2020
DOI: 10.31091/jomsti.v3i1.959
|View full text |Cite
|
Sign up to set email alerts
|

Meyer’s Approach on Musical Analysis and Its Relevance to Indonesian Analytical Study of Western Music

Abstract: This critical review of Leonard Bunce Meyer's musical analysis theory is aimed at obtaining a basic understanding of an approach that seems uncommon in Indonesian studies of Western music. This study uses a speculative method with descriptive as well as critical approaches, where Meyer's analysis theory is depicted critically by conforming it toward Nicolas Cook's critical review which was based on the Shenkerian concept. The relevance application of this analysis model in the studies of musical form in Indone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…First and foremost, the survey data showed that mothers utilized recorded music to fulfill various emotional needs in their everyday lives. Consistent with previous studies (Trehub and Schellenberg, 1995;Ilari, 2005;Trehub et al, 2010), children's mood and states were often used as indicators of when and what kinds of music mothers put on. Overall, mothers tended to use music to maintain or reinforce their child's positive mood rather than to improve a negative mood, given that out of the 197 episodes, only 26% were related to situations when children were in uncomfortable states physically and/or mentally.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…First and foremost, the survey data showed that mothers utilized recorded music to fulfill various emotional needs in their everyday lives. Consistent with previous studies (Trehub and Schellenberg, 1995;Ilari, 2005;Trehub et al, 2010), children's mood and states were often used as indicators of when and what kinds of music mothers put on. Overall, mothers tended to use music to maintain or reinforce their child's positive mood rather than to improve a negative mood, given that out of the 197 episodes, only 26% were related to situations when children were in uncomfortable states physically and/or mentally.…”
Section: Discussionmentioning
confidence: 53%
“…Parents are known to listen to music with young children for similar reasons, oftentimes with expectations that music will positively impact their youngsters' lives (Lamont, 2008). Music has been used to regulate mood and behaviors of infants, young children and their caregivers (Trehub and Schellenberg, 1995;Shenfield et al, 2003;Trehub et al, 2010). But unlike some adults who often sit and listen quietly to a musical piece, young children are known to listen to music in idiosyncratic ways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation